Optical Properties of Dye-Filled Polymer Films Deposited in Vacuum - Grytsenko, K.; Navozenko, O.; Kolomzarov, Yu.; Kryuchin, A.; Tolmachev, O.; Slominsky, Yu.; Kurdukov, V.; Ksianzou, V.; Schrader, S. (Реєстрація, зберігання і обробка даних, 2012)
The results of investigating properties of polytetrafluoroethylene (PTFE) and polyparaphenylene sulphide (PPS) films filled with dye molecules by co-deposition in vacuum are given. Thin polymer films filled with different polymethine dyes with various dye concentration are investigated. Film properties at room temperature and during heating were studied using optical absorption spectroscopy. It is shown that the polymer matrix prevented dye molecules aggregation, particularly the PTFE matrix prevented aggregation more strongly than the PPS matrix. During heating the PTFE matrix keeps the dye molecules in non-aggregated state up to dye decomposition temperature.